Pirate Nests and the Rise of the British Empire, 1570-1740 - Hanna, Mark G., 1974- (Book collections on Project MUSE., 2015)
"Analyzing the rise and subsequent fall of international piracy from the perspective of colonial hinterlands, Mark G. Hanna explores the often overt support of sea marauders in maritime communities from the inception of England's burgeoning empire in the 1570s to its administrative consolidation by the 1740s. Although traditionally depicted as swashbuckling adventurers on the high seas, pirates played a crucial role on land. Far from a hindrance to trade, their enterprises contributed to commercial development and to the economic infrastructure of port towns."--